On continuity of choice: the places and spaces visited by tourists and travellers in Portugal in the 18th and 19th centuries - Conde, Antónia Fialho (2010)
A comparison of the tourist resorts chosen by visitors to Portugal with the places described in accounts of journeys and in travel guides since the 18th century reveals a high degree of continuity as regards preferences for certain spaces, including monasteries, convents and palaces, as well as the respective surroundings. They form what might be termed a “classic itinerary”, which includes the sites in Portugal which were regarded, and still are, as most worth visiting for their great historical and artistic interest and importance. Times have changed and new forms of tourism are now the fashion: tourist attractions are seen from a different perspective and travellers seek out new places and refuges, rural paradises, exotic shores and regional gastronomic delights. The preferred itinerary of those who visit Portugal today, just like that of 18th-century travellers, still takes in the monasteries of Alcobaça, Batalha and the Hieronymites, the convent of Mafra, and Sintra palace and its surroundings. In this paper we seek to highlight the following aspects by means of the comparison of the recommendations contained in contemporary travel guides and 18th-century travellers’ accounts: - the reasons why travellers and tourists in each era include these spaces in their Portuguese travel itineraries (architectural importance, the artistic style with which they are associated, the beauty of the landscape, and their singular features as social and leisure spaces); - the opinions expressed on them by tourists and travellers in each era; - the way in which the descriptions of experiences encourage or encouraged other travellers and tourists to chose the same destinations.